Efeito de duas intervenções com atividade física em sala de aula sobre o desempenho cognitivo e indicadores de saúde de crianças do ensino fundamental - Melo, João Carlos do Nascimento (2024)
Introduction: Intervention strategies such as active breaks and physically active lessons have shown promising effects in reducing sedentary behavior and improving academic performance. However, significant scientific gaps persist, particularly regarding the effects on cognitive function. Additionally, there is a scarcity of evidence from middle- and low-income countries like Brazil, and few studies compare diverse types of interventions, limiting the understanding of the relative effectiveness of these strategies. Objective: To investigate the effectiveness of active breaks and physically active lessons on cognitive function and health indicators in elementary school children. Methods: This study is a cluster-randomized clinical trial conducted in municipal schools in Aracaju, SE. Six schools were randomly assigned to three groups: 1) Active Breaks (2 schools with 6 classes, n=61) with 5 to 10-minute movement breaks between lessons to interrupt sitting time; 2) Physically Active Lessons (2 schools with 5 classes, n=77) combining movement with pedagogical content; and 3) Control (2 schools with 5 classes, n=46) following the traditional curriculum. The interventions took place over 8 weeks, from September to November 2022. Cognitive function was assessed by reaction time and total correct responses in five computerized tests: Visual Search (visual attention), Go/NoGo (inhibitory control), Mental Rotation (mental rotation), Posner Cueing (visual attention), and Digit Span (working memory). Physical activity was assessed objectively by pedometers and subjectively by the Web-CAAFE questionnaire. Quality of life was measured by the quality of life assessment scale (AUQEI), daytime sleepiness by the pediatric daytime sleepiness scale (PDSS), and school perception by a questionnaire with responses on a five-point visual analog scale. Generalized Estimating Equations models adjusted for age and sex were used to verify the effect of interactions over time. Statistical analyses were conducted in R, with a significance level of 5%. Results: In inhibitory control, there was a significant reduction in reaction time in the physically active lessons group (p<0.001), with no differences in the active breaks (p=0.991) and control (p=0.425) groups. For visual attention, there were significant changes in the total correct responses in the Cueing test for the physically active lessons group (p=0.014), but not for the active breaks (p=0.078) and control (p=0.405) groups. There was also a significant reduction in reaction time in the physically active lessons group (p<0.001), but not in the active breaks (p=0.222) and control (p=0.112) groups. In working memory, there was a significant increase in total correct responses in the physically active lessons group (p<0.001), while the active breaks (p=0.797) and control (p=0.816) groups showed no significant differences. There was a significant increase in daytime sleepiness symptoms in the physically active lessons group (p<0.001), with no differences in the active breaks (p=0.641) and control (p=0.324) groups. No significant changes were observed in the other variables. Conclusions: The findings suggest that physically active lessons are an effective intervention for improving inhibitory control, working memory, and visual attention in first-year elementary school children.